Pengaruh Teknologi Artificial Intelligence Pada Layanan Chatbot Shopee Terhadap Kepuasan Pelanggan di Bandung Raya, Indonesia - Alghaniy, Aflah Malik (Asosiasi Ahli Administrasi Indonesia, 2024)
This study aims to outline the indications of the influence of artificial intelligence technology on Shopee's chatbot service on customer satisfaction. Involving 111 respondents scattered across the Greater Bandung region, the research focuses on those who have used or frequently used Shopee's chatbot service (Choki). The analytical methods employed include a descriptive approach, utilizing correlation and multiple regression as tools. The research findings indicate that artificial intelligence technology in Shopee's chatbot service has a significant influence of 48.2%, while the remaining 51.8% is influenced by other factors.